Germicidal activity of antimicrobials and VIOlight ® Personal Travel Toothbrush Sanitizer: An in vitro study - Beneduce, C.; Baxter, K.A.; Bowman, J.; Haines, M.; Andreana, S. (Journal of dentistry, 2010)
The study evaluated the antibacterial effect of VIOlight ® (VL) Personal Travel Toothbrush Sanitizer on biofilms after toothbrush exposure to human saliva compared to Listerine ® Antiseptic (LA), 3% hydrogen peroxide (3%HP) and water. Twenty toothbrush heads ( n = 5/Gp) were immersed in saliva and to allow for bacterial growth and biofilm formation for 24 h. VL sanitizer and antiseptic(s) were used for 7 min; after treatment, brush heads were rinsed and placed into 10 mL of 2× AOAC Letheen Broth, sonicated and vortexed for 10 s. Tenfold serial dilutions were prepared and plated and incubated aerobically and anaerobically. Log 10 CFU/mL data were compared utilizing ANOVA ( p < 0.05). Results showed 3%HP with significantly lower counts than LA, VL and control for aerobic and anaerobic bacteria. LA had significantly lower counts than VL and control for both types of bacteria and VIOlight ® had significantly lower counts than the control for aerobic bacteria. 3%HP and LA were most effective in rapidly killing bacteria when compared to VIOlight ®. Results showed that 3% hydrogen peroxide was most effective in reducing the numbers of both aerobic and anaerobic bacteria present on the toothbrush heads. Under the same test conditions, Listerine ® Antiseptic was shown to be secondarily effective for the same bacteria while the VIOlight ® unit was the least effective when compared to the other treatment groups.